Follicular carcinoma of the thyroid minimally invasive - Delgado, Bolívar; Santandreu, Jorge (Cirugía del Uruguay, 1999)
An analysis is carried out on the therapeutic problem of the minimally invasive capsulated follicular carcinoma relating it to risk groups.